Surface electromyography characteristics of patients with anterior cruciate ligament injury in different rehabilitation phases - Cui, Hongxing; Cao, Zhijie; Wang, Shanshan; Zhang, Hao; Chen, Ze; Wu, Xipeng; Zhao, Yixuan; Qie, Shuyan; Li, Wei (Frontiers in Physiology, 2023)
Background: Anterior cruciate ligament reconstruction (ACLR) is a common treatment for anterior cruciate ligament (ACL) injury. However, after ACLR, a significant proportion of patients do not return to pre-injury levels. Research on muscle function during movement has important implications in rehabilitation. Methods: Sixty patients with unilateral ACL injury were recruited for this study and categorized into three groups as follows: group A, individuals with an ACL injury before half one year; group B, individuals with ACLR from one year to one year; and group C, individuals with ACLR one year later. The surface electromyography (SEMG) signals were collected from the bilateral rectus femoris (RF), vastus medialis (VM), vastus lateralis (VL), biceps femoris (BF), and semitendinosus (ST). The tasks performed during the experiment included straight leg raising (SLR) training at 30°, SLR training at 60°, ankle dorsiflexion, walking, and fast walking. Results: In the maximum muscle strength test, the affected side of the BF in group A was significantly larger than that in group B and group C. In the walking test, the contralateral side of RF in group B was significantly larger than that in group C. In the SLR training (60°) test, the contralateral side of RF in group C was shown to be significantly larger than that in group A and smaller than that in group B; In the ankle dorsiflexion training test, the contralateral side of RF in group B was significantly larger than that in group C. Conclusion: This study showed the EMG characteristics of patients with an ACL injury, which helped us to determine which muscle requires more training and which exercise model is best suited according to the results.